The use of transmission electron microscopy and oocyte transfer to evaluate in vitro maturation of equine oocytes in different culture conditions - Fernandes, C. B.; Peres, K. R.; Alvarenga, Marco Antonio [UNESP]; Landim-Alvarenga, F. C. (Elsevier B.V., 2006)
The current study evaluates the ability of equine oocytes matured in different conditions to undergo nuclear and cytoplasmic maturation.. After oocyte transfer, embryonic development was diagnosed at 1.5 and 90 days of gestation. For each group, immature oocytes obtained from slaughterhouse ovaries were matured in vitro (5 replicates). In experiment I, three different media were tested. HTF:BME, SOFaa, and TCM 199. In experiment 11, the HTF:BME was chosen as maturation medium containing pFSH, eFSH, or eFSH + eGH. Nuclear maturation was estimated after stripping the oocytes and staining with Hoechst 33342. The evaluation of cytoplasmic maturation was performed by transmission electron microscopy. For oocyte transfer, six non-cycling recipient mares were used, and 8 to 15 oocytes were transferred in each mare. In experiment I, the results showed no differences (P > .05) in nuclear maturation (MII) among experimental groups. The percentage of MII was 29.3 ( +/- 9.6), 23.4 ( +/- 8.4), and 13.5 ( +/- 12.4) for HTF:BME, SOF, and TCM, respectively. In experiment II, all media tested were efficient in inducing metaphase II. Also, no statistical differences (P > .05) were observed in percentages of nuclear maturation rates when porcine (37.1 +/- 22.4) or equine (25.8 +/- 8.2) FSH were used, or when eFSH + eGH was added to HTF:BME (29.4 +/- 12.3). The analysis of cytoplasmic morphology of oocytes cultured in TCM 199 and SOFaa showed signs of incomplete cytoplasmic maturation and premature cortical reaction. Meanwhile, oocytes cultured in HTF:BME medium presented cytoplasmic characteristics similar to those described by others for in vivo-matured oocytes. The addition of eFSH to the HTF:BME medium resulted in an improvement of cytoplasmic morphology. After oocyte transfer, two mares became pregnant, one from pFSH group and one from eFSH+eGH group. These results indicate that although in vitro matured equine oocytes are capable of fertilization and embryonic development, the percentage of competent oocytes is still low.
Keywords: transmission electron microscopy; equine oocyte maturation; oocyte transfer; ultrastructure